1956
DOI: 10.1038/177238a0
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Calcium Superoxide

Abstract: by Dent•. 500 µl. of deproteinized and desalted plasma, and amonnts of desalted urine corresponding to 250 µgm. of total nitrogen (Kjeldahl), were spotted on to 60-cm. squares of Whatman No. 4 paper,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1961
1961
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
4
20
0
Order By: Relevance
“…2, indicating that the crystal structure of the compound is uncertain. We note, moreover, that the earlier structures proposed by Kotov et al (7) and Brosset et al (8) have not been confirmed. In addition, calcium peroxide has never been prepared in a pure form: all samples contain water and/or hydrogen peroxide, since the synthetic preparations use water as a solvent and hydrogen peroxide as one of the starting materials (7).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…2, indicating that the crystal structure of the compound is uncertain. We note, moreover, that the earlier structures proposed by Kotov et al (7) and Brosset et al (8) have not been confirmed. In addition, calcium peroxide has never been prepared in a pure form: all samples contain water and/or hydrogen peroxide, since the synthetic preparations use water as a solvent and hydrogen peroxide as one of the starting materials (7).…”
Section: Introductionmentioning
confidence: 62%
“…The calcium carbide structure has also been proposed for CaO (7,8). The structural investigations are based on powder diffraction data of poorly crystalline samples and show additional weak reflections which cannot be attributed to the calcium carbide structure (5,7), as shown in Fig.…”
Section: Introductionmentioning
confidence: 98%
“…) and one Aquatic Warbler was among the corpses found by Cott on an outlier of the eastern Canary Islands (Bannerman 1931). Brosset (1956) recorded Aquatic Warblers as common in marshes in northeastern Morocco for a few days in both autumn and early spring. The sole Egyptian record is on sight, by Meiklejohn (1944) at Ismailia, on the Canal.…”
Section: Acrocephalus Schoenobaenus Sedge Warblermentioning
confidence: 99%
“…The slope then refers to the number of defects formed in the originally stoichiometric solid by an accommodation of 2 oxygen atoms (from the 02 molecule) subjected to the electroneutrality condition. The problem is, however, that the simple ionic defect reaction of this type: 02 + Vi + 2Cu~u ~ Oi" + 2Cucu (16) gives a slope of 6 instead of 3. Such a serious disagreement is usually attempted solved by abandoning the assumption of the ionicity from the defect model and/or considering defect clusters instead.…”
Section: Equilibriummentioning
confidence: 95%
“…This should be taken into consideration in the evaluation of the oxygen dissociation pressure, which will vary with the content of peroxide in the solid-solution phase [13]. To illustrate rough trends, equilibrium oxygen pressures for SrO1.97 [12], and for the oxide-saturated barium peroxide are expressed (p in Pa, Tin K) [12,13] The peroxides crystallize [14,15] with the CaC2-type structures: CaO2 {P4/mmm; 356, 596} [16], SrOz {355,655} [17] and BaO2 {381.14(6), 682.15(11)} [15].…”
Section: ( 9 701mentioning
confidence: 99%